Rockfall hazard assessment based on airborne laser scanning data and GIS in tropical region - Fanos, Ali Mutar (2016)
Rockfall is one of the catastrophes which threaten the human's life and properties in mountainous and hilly regions such as Malaysia with steep and high elevation topography. Prediction and mitigation of such phenomenon can be carried out via the identification of rockfall source areas and modelling of rockfall trajectories and their characteristics. Therefore, a proper rockfall analysis method is required in order to map and thus understand the characteristics of rockfall catastrophe. This research adopted various methods to investigate, analyze and assess rockfall in terms of identification of rockfall source areas, modelling of rockfall trajectories and their characteristics and consequently rockfall hazard map. A portion of North-South Expressways at Jelapang, Malaysia was used as a study area for rockfall hazard assessment. An airborne laser scanner (ALS) was used to gather high-density data point (3-4 pts/m²). After postprocessing in terms of filtration, interpolation and fill, high-resolution DEM (0.5m) was generated. In this study, rockfall source areas were identified using multi-criteria method based on DEM derivates, terrain type or land use/cover (LULC) and high spatial resolution aerial photo (13cm). After the rockfall source areas were identified, rockfall modelling has been done using 3D rockfall model integrated into GIS software. Rockfall modelling processes are carried out through discrete time steps kinematic algorithms that are automatically determined by both particle velocity and cell size. Kinematic algorithms allow rockfall modelling in different motion modes in a 3D frame. Mechanical parameters (coefficients of restitution tangential (Rt) and normal (Rn) and friction angle) were considered to be crucial for rockfall modelling. Multi rockfall scenarios were produced based on a range of mechanical parameters values. Rockfall spatial distribution modelling technique was utilized to display the rockfall spatial distribution frequency, bouncing or flying height and kinetic energy for each scenario according to the outcomes of 3D rockfall process modelling. The hazard map predicting rockfall hazard for each scenario was produced by using of spatial modelling which considers all raster of the rockfall characteristics. Analytic hierarchy process (AHP) was applied in this step to get the weight for each rockfall characteristics raster. The rockfall hazard along the expressway was observed and the hazard percentage was demonstrated. The result shows rockfall behaviour is highly affected by mechanical parameters values. It clears that when the values are big, the rockfall trajectories have the longest stopping distance and more complicated behaviour which result in increasing of rockfall characteristics. This results in rising of the areas affected byrockfall hazard. In addition, in order to mitigate rockfall hazard, a barrier location was suggested based on less bouncing height and energy. The entire simulation procedure was repeated with a barrier to show the efficiency of barrier eliminating rockfall hazard. The result shows the barrier in suggested location can effectively aid in rockfall hazard mitigation. The outcomes of this study prove the ability of the proposed and applied methods to make valid detection and prediction for rockfall phenomena. The results are expected to not only provide a quick comprehensive assessment of future rockfall hazards and risks but also serve as a guide for barrier designers. The applied methods and information will add a valuable contribution to the rockfall management in the tropical Malaysia